The Effect of Counseling Using Leaflet Media on the Level of Compliance of Pregnant Women with Iron Consumption - Sela, Fitria; Simarmata, Mesrida; Sinaga, Asnita; Zega, Petra Diansari; Nurliana, Elly (Institute Of Computer Science (IOCS), 2024)
Anemia is rate Hemoglobin in blood below normal. Possible impact _ happened to the mother pregnant so mother and fetus like bleeding moment childbirth and abortion, LBW even death fetus. Need given intervention in mothers pregnant: gift counseling use leaflet. Type study This is intervention. Design true experiment. Design study use pre-test and post test in one group. Population is all over Mother Anemic pregnant women at the Elly Clinic, Klambir V Village, Deli Serdang in 2023, totaling 40 mothers. Amount sample used _ were 40 people obtained with use technique Total sampling. The sample consists of 20 mothers pregnant group treatment use leafleat and 20 mothers pregnant group control without use leaflet. Data analysis techniques use tests Independent t-test . Compliance Mother pregnant with counseling without leaflet is mean value 54.65 and compliance Mother pregnant consumption of substance tablets iron with counseling use leaflet is increase after 76.50. There is improvement obedience Mother consuming substance tablets iron that is p =0.000 < of ? value = 0.05. There is improvement in consume iron tablets after get counseling use leaflet.